"I've Struggled, I've Battled": Invisibility Microaggressions Experienced by Women of Color at a Predominantly White Institution. Issue 3 (2nd September 2017) - Mena, Jasmine A.; Vaccaro, Annemarie
Abstract : This study used critical ethnography to document microaggressions experienced by women Staff and Faculty of Color at a predominantly White institution of higher education. This article focuses on invisibility, a specific type of microaggression, which emerged as a prominent finding. Participant narratives explicated three manifestations of environmental microaggressions (campus, disciplinary/professional, and community invisibility) and two forms of interpersonal microaggressions (professional and leadership invisibility). Recommendations for higher education professionals are provided.